2019
DOI: 10.3390/nano9091203
|View full text |Cite
|
Sign up to set email alerts
|

N/S-Co-Doped Porous Carbon Sheets Derived from Bagasse as High-Performance Anode Materials for Sodium-Ion Batteries

Abstract: Heteroatom doping is considered to be an efficient strategy to improve the electrochemical performance of carbon-based anode materials for Na-ion batteries (SIBs), due to the introduction of an unbalanced electron atmosphere and increased electrochemical reactive sites of carbon. However, developing green and low-cost approaches to synthesize heteroatom dual-doped carbon with an appropriate porous structure, is still challenging. Here, N/S-co-doped porous carbon sheets, with a main pore size, in the range 1.8–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The corresponding fitted parameters of equivalent circuits are shown in Table S4, Supporting Information). It is notable that NBT700 has the smallest semicircle ( R ct = 14.3 Ω) due to large surface area, enlarged interlayer space and ultrathin nanosheets structure, implying the fastest charge‐transfer process 12,27. The galvanostatic intermittent titration technique (GITT) was applied to investigate the diffusivity coefficient of Na + for NBT700 and NDC at 0.05 A g −1 with a pulse current for 0.5 h between rest intervals for 1 h (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding fitted parameters of equivalent circuits are shown in Table S4, Supporting Information). It is notable that NBT700 has the smallest semicircle ( R ct = 14.3 Ω) due to large surface area, enlarged interlayer space and ultrathin nanosheets structure, implying the fastest charge‐transfer process 12,27. The galvanostatic intermittent titration technique (GITT) was applied to investigate the diffusivity coefficient of Na + for NBT700 and NDC at 0.05 A g −1 with a pulse current for 0.5 h between rest intervals for 1 h (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…[ 40 ] Moreover, the heteroatom of sulfur is also offered to improve electrode kinetics by creating CSC covalent bond, and given additional active sites for Li + , it improves the reversible capacity by affecting the interlayering of carbon. [ 41 ] For example, recently, Jiang and coworkers [ 37 ] prepared sulfur‐doped honeycomb‐like 3D porous carbon (SHC) using bagasse waste as the carbon source and elemental sulfur as S source. Initially, biogases waste was heated at 300 °C for 2 h, and after that, this material was mixed with elemental sulfur then heated at 800 °C for 2 h under argon atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution of V 2p spectrum (Figure 3a) displays four components, corresponding to the V 2+ and V 3+ , respectively [7,23]. In Figure 3b, S 2p spectrum exhibits obvious three peaks, which can be assigned to the typical M–S (M = metal), C–S, and common S–O bonds [8,9,24,25]. However, the S 2p spectrum of VS/NSG suggested that the S-doped graphene had been affected by the presence of sulfides.…”
Section: Resultsmentioning
confidence: 99%